The multidisciplinary approach to the treatment of paediatric chronic pain: a qualitative analysis through focus groups - Aldana Paola Ercolano; Sabrina Galvan; Tessa Louise Marchesan; Alessia Gavioli; Gerardo Papa; Mariarita Todaro; Lidia Berforini D’Aquino; Alessia Zanatta; Andrea Vianello (Journal of Biomedical Practitioners)
Background: Access to pain care is recognized as a fundamental human right, ratified by Law 38/2010 and supported by the professional codes of conduct for healthcare practitioners. Pain, defined by the International Association for the Study of Pain (IASP), as an unpleasant sensory and emotional experience associated with actual or potential tissue damage. It becomes chronic when it persists beyond three months, affecting quality of life and clinical prognosis. The World Health Organization (WHO) has recently promoted a multidisciplinary approach for pediatric chronic pain, integrating physical, psychological, and pharmacological interventions, given the high prevalence of pain in pediatric populations, affecting up to 46% of children and adolescents. However, recent studies highlight gaps in healthcare providers’ competencies in managing pediatric chronic pain, and the need to update professional training and explore further non-pharmacological approaches to improve its management.